Executive Committee Minutes 2005-10-20 - Academic Senate:::::::::
B. S. in Bio-Chemistry, Senate Self-Study, Spring Convocation, Senate Unit Allocation – 3 & 4 unit courses, Advising Survey, Faculty Retreat Topic, Emeritus Dinner